2008
DOI: 10.1016/s0140-6736(08)61348-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between the SERPING1 gene and age-related macular degeneration: a two-stage case–control study

Abstract: Summary Background Age-related macular degeneration is the most prevalent form of visual impairment and blindness in developed countries. Genetic studies have made advancements in establishing the molecular cause of this disease, identifying mutations in the complement factor H (CFH) gene and a locus on chromosome 10 encompassing the HTRA1/LOC387715/ARMS2 genes. Variants in complement 3 (C3) and an HLA locus containing both factor B and C2 genes have also been implicated. We aimed to identify further genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 29 publications
6
109
0
1
Order By: Relevance
“…77 Subsequent studies using seven independent cohorts of AMD patients and controls failed to replicate the association with the gene variants. 78 However, a further independent study of neovascular AMD and disease-free controls 79 has recently replicated the original Ennis et al 76 findings, noting that the previous replication groups were of mixed phenotype. The SERPING1 association remains controversial, but if it becomes established, this is the first indication that the classical complement pathway may be involved in AMD pathogenesis.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 83%
See 1 more Smart Citation
“…77 Subsequent studies using seven independent cohorts of AMD patients and controls failed to replicate the association with the gene variants. 78 However, a further independent study of neovascular AMD and disease-free controls 79 has recently replicated the original Ennis et al 76 findings, noting that the previous replication groups were of mixed phenotype. The SERPING1 association remains controversial, but if it becomes established, this is the first indication that the classical complement pathway may be involved in AMD pathogenesis.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 83%
“…A candidate gene study of complement genes by Ennis et al 76 showed an association between (mainly neovascular) AMD with SNPs in the promoter and introns of serpin peptidase inhibitor, clade G, member 1 (SERPING1), in both a UK and a USA cohort of patients. The authors showed that the gene, which is an inhibitor of complement component 1, is expressed in the retina.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 99%
“…SERPINF2 modulates insulin sensitivity and is associated with cardiovascular diseases and diabetes (Aso et al., 2000; Uitte de Willige et al., 2011). SERPING1 modulates the complement cascade and is important in many inflammatory diseases, including macular degeneration (Ennis et al., 2008). SERPINA3 has been identified as a specific biomarker of delirium and Alzheimer's disease (Padmanabhan, Levy, Dickson, & Potter, 2006; Poljak et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas mechanistic studies have shown that inflammation (1) and smoking (2) are fundamental components of AMD, genetic studies have demonstrated that polymorphisms in different complement proteins each increase the risk for developing AMD. Genetic variations with a number of complement components, including those of required activators (complement factor B, CFB) (3), inhibitors (complement factor H, CFH (4 -6); complement 1 inhibitor, C1INH, although the evidence is conflicting (7,8)) and essential components in the complement cascade (complement factor 2 and 3, C2 (3) and C3 (9)) have been found to be associated with all forms of AMD. In particular, one of the most detrimental mutations occurs in CFH (fH risk haplotype).…”
mentioning
confidence: 99%